Investigation of the Effect of Roof Color on the Energy Use of a Selected House in Amman, Jordan - Alrwashdeh, Saad S.; Qadourah, Jenan Abu; Al-Falahat, Ala’a M. (Frontiers in Mechanical Engineering, 2022)
The building sector is considered one of the most important energy-consuming sectors in Jordan, as the causes of energy consumption differ according to the purpose of the buildings, their areas, and the technologies used in them. In this research, the use of different colors to paint the roof surface of buildings and the study of the effect of paint color on energy gain from solar energy throughout the year was studied. It was found that the best paint colors for energy conservation is white and the worst in energy conservation is black